Peningkatan Kualitas Produk Mocaf melalui Penerapan Alat Produksi dan Pemasaran Produk - Ika Romadoni Yunita, Ika Romadoni Yunita; Zanuar Rifai, Zanuar; Fiby Nur Afiana, Fiby Nur Afiana (CERED Indonesia Publishing, 2025)
Pangebatan Village has great potential in cassava production, which is a superior food crop in the region. However, its utilization has not been optimal, especially in processing it into mocaf flour. BUMDes Berkah Sentosa which manages this potential still faces various challenges, such as limited production, human resources, technology, and marketing. To overcome these problems. Amikom University of Purwokerto through the Community Service (PKM) program funded by the Ministry of Education, Culture, Research and Technology in the 2025 funding year provides assistance covering three main areas: production (procurement and use of dryhouses for cassava drying), management (human resources training and product certification), and marketing (online-offline promotion and expansion of market reach). The activities take place in stages from July to the end of 2025, involving lecturers and students of Amikom University of Purwokerto, with the main target of improving production quality, competitiveness of mocaf products, and the welfare of the Pangebatan Village community.